Death Penalty to Drug Traffickers from the Perspective Ofsiyāsah Syar’iyyah - Wan Norhasnih Wan Husin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
In Malaysia, drug abuse and drug trafficking began affecting thesociety seriously around the 70s and, the trend has continued unabatedly in thefirst decade of the new millennium. The outcomes are staggering, as it is thecause of various social ills such as murder, burglary, prostitution, and evencauses family disintegration and erodes social relations. The main objective ofthis study is to analyze from the Islamic perspective on the death penalty basedon the siyāsah Syar’iyyah principles since the punishment by death for drugtrafficking is not an offence directly stated in the al-Quran and al-Sunnahunder the hudud law. Based on textual analysis, the study finds that the deathpenalty meted out against drug traffickers is justified based on the severity ofthe act in affecting the individual involved, society and the nation.